2017
DOI: 10.1152/ajpheart.00080.2016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determination of the vascular reactions in humans in response to the diving reflex

Abstract: The purpose of this study was to investigate the genetic mechanisms of the defense vascular reactions in response to the diving reflex in humans with polymorphisms in the genes , and We hypothesized that protective vascular reactions, in response to the diving reflex, are genetically determined and are distinguished in humans with gene polymorphisms of the renin-angiotensin and kinin-bradykinin system. A total of 80 subjects (19 ± 1.4 yr) participated in the study. The intensity of the vascular response was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
0
18
0
3
Order By: Relevance
“…An increase in the sympathetic noradrenergic effects on the alpha-1 receptors of muscle cells of peripheral vessels leads to a constriction of the vessels of the skin and organs of the gastrointestinal tract. Blood flow is redistributed to the lungs, heart, and brain (Heusser et al, 2009;Baranova et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the sympathetic noradrenergic effects on the alpha-1 receptors of muscle cells of peripheral vessels leads to a constriction of the vessels of the skin and organs of the gastrointestinal tract. Blood flow is redistributed to the lungs, heart, and brain (Heusser et al, 2009;Baranova et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although these disparities may be partly attributed to a training-induced effect (Joulia et al 2002 , 2003 ; Schagatay et al 2000 ), accumulating evidence suggests they may also stem from selective genetic variations (Baranova et al 2017 ; Ilardo et al 2018 ). Baranova et al ( 2017 ) observed that during a maximal apnoeic attempt, individuals with a combination of the C/C allele of the bradykinin receptor B2, D/D allele of the angiotensin-converting enzyme, and G/G polymorphism in the renin genes exhibited: (i) a more pronounced vasoconstriction, (ii) a lower blood supply to peripheral vessels, (iii) a lower pulse wave amplitude and (iv) lower pulse transit time values compared with heterozygous individuals. Conjointly, these genetic polymorphisms augment the release of angiotensin-II and suppress endothelial nitric oxide synthase through the degradation of bradykinin.…”
Section: Apnoea and The Diving-responsementioning
confidence: 99%
“…As current technology refines and new technologies are born, new discoveries are forthcoming concerning the enigmatic mammalian DR. Indeed, genetic studies are now underway illustrating how diving mammals, including humans, have adapted to their anoxic underwater environments (Fabrizius et al, 2016;Baranova et al, 2017;Hoff et al, 2017;Ilardo et al, 2018;Zhou et al, 2018;Xu et al, 2019). Introduction of the DR in the mouse (Hult et al, 2019) provides opportunity for an entirely novel set of techniques for genetic manipulation of neurons.…”
Section: The Diving Response In the Humanmentioning
confidence: 99%